Semiotics of the discourse: balance and perspectives - Fontanille, Jacques (2008)
This paper investigates the way in which the concept of “discourse” is used by some branches of the discourse analysis and the Greimassian semiotics. After the identification and the analysis of some epistemological trends in the definition of “discourse”, the constituents of a semiotics of the discourse guided for the tensivity and the sensitivity are presented summarily. Keywords: greimassian semiotics. tensive semiotics. epistemology. discourse. text.